Chicken Feathers. 98 - Sweeney, Shel (Singapore : English Corner Publishing Pte Ltd., 2019)
Science Adventures is an ongoing series of science themed comic magazines, originally published in Singapore, to promote science and language skills amongst primary school students. These full-colour magazines are designed to stimulate children's interest in science and STEM subjects. Issue 61 onwards began adding art-themed comics to expand the focus to STEAM. These later issues also conform with Cambridge International Primary Years Programme for Science and with NESA s NSW Syllabus for the Australian Curriculum.
Includes practice questions
Made in Singapore for the World -- Cover
Based on Science themes: STEAM (Science, Technology, Engineering, Arts and Math)
Science Comic for ages 9-10
Keywords: Comic books, strips, etc -- Science -- Singaporean; Comic books, strips, etc